Mangunjaya, Ancient Region of the Sultanate of Jambi - Shofiyah, Shofiyah; Halim, Abdul; Rahman, Fuad (International Journal of Advanced Multidisciplinary, 2025)
Mangunjaya Ancient Region of Jambi Sultanate is a scientific article of literature study in the scope of the field of science. The purpose of this article is to trace the origins and development of the Mangunjaya region as part of the government structure of the Jambi Sultanate, preserve cultural heritage, support education and research, increase public understanding of the importance of local history and encourage participation in the preservation of cultural heritage. The object of research is online libraries, ancient manuscripts, ancient records and the Bukit Siguntang site along with all the historical, cultural and physical elements attached to it. The research method with library research is sourced from ancient manuscripts and records. Qualitative descriptive analysis. The results of this article: 1) show that the site has significant historical and cultural value, related to Malay civilization. 2) This study reveals that Mangunjaya is a form of local wisdom that still survives in the former Jambi Sultanate, especially in the interior areas that still uphold customary values. This tradition is deeply rooted in the Jambi Malay cultural system and is closely related to the social and religious structure of the local community. 3) archaeological findings such as Buddha statues, inscriptions, and ancient ceramics that support its important role in the history of the region.